1992
DOI: 10.1002/app.1992.070440605
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of alkyl, ester, carboxylate, amino, hydroxyl, and phosphate functional groups to the surface of polyethylene

Abstract: SYNOPSISThe surface of polyethylene was derivatized with ester, carboxylate, amino, hydroxyl, and phosphate functional groups. 01, w bifunctional alkanes, containing on one end a primary amine, were coupled to oxidized polyethylene through an amide linkage. Polyethylene was first oxidized with chromic acid, the carboxylate groups were converted to the acyl chloride with phosphorus pentachloride, and then reacted with a primary amine to give the covalently bound amide. The copposing ends of the bifunctional alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Therefore the total number of grafted hydrophilic groups on PEAA-PA (phosphate) and PEAA-PS (carboxyl and phosphate) were similar at their highest grafting percentages. In several instances [32,33], it has been shown that phosphate groups are more hydrophilic than carboxylic acid group. One or two water molecules can form hydrogen bonds with a carboxyl group [34], whereas three or more water molecules can form hydrogen bonds with a phosphate group [35].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the total number of grafted hydrophilic groups on PEAA-PA (phosphate) and PEAA-PS (carboxyl and phosphate) were similar at their highest grafting percentages. In several instances [32,33], it has been shown that phosphate groups are more hydrophilic than carboxylic acid group. One or two water molecules can form hydrogen bonds with a carboxyl group [34], whereas three or more water molecules can form hydrogen bonds with a phosphate group [35].…”
Section: Resultsmentioning
confidence: 99%
“…This study investigates an easily accessible, cost‐effective polymeric material with improved properties, which dissipates static charge and renders the material more susceptible to common dyestuff, while retaining the essential mechanical properties of low‐density polyethylene for its intended use in technical textiles . Polyolefins films have been treated with mineral acids under different reaction conditions in order to achieve a rough film surface and to introduce polar groups . Common polyolefin are used in the packaging industry and most of the research work reported in the literature is related to only chemical surface treatment of films .…”
Section: Introductionmentioning
confidence: 99%
“…XPS measurements, also referred to in the literature as ESCA (electron spectroscopy for chemical analysis), have been performed on polyethylene by a variety of authors [4,[5][6][7]24], employing a variety of surface treatments including exposure to corona discharge, plasma etching, and electrochemical exposure (oxidizing electrolytes). Oxidation products could be detected by two different measurement systems: presence of the O1s binding energy, or higher energy shoulder on the C1s binding energy curve, indicating a change in bonding environment for the carbon atoms [7].…”
Section: Surface Analysis Of Oxidized Polyethylenementioning
confidence: 99%